Multiple Transport Pathways for Mediating Intracellular pH Homeostasis: The Contribution of H+/ion Exchangers - Pittman, Jon (Frontiers in Plant Science, 2012)
Intracellular pH homeostasis is an essential process in all plant cells. The transport of H+ into intracellular compartments is critical for providing pH regulation. The maintenance of correct luminal pH in the vacuole and in compartments of the secretory/endocytic pathway is important for a variety of cellular functions including protein modification, sorting, and trafficking. It is becoming increasingly evident that coordination between primary H+ pumps, most notably the V-ATPase, and secondary ion/H+ exchangers allows this endomembrane pH maintenance to occur. This article describes some of the recent insights from the studies of plant cation/H+ exchangers and anion/H+ exchangers that demonstrate the fundamental roles of these transporters in pH homeostasis within intracellular compartments.